Application of percutaneous lymphatic contrast-enhanced ultrasound in lymphovenous anastomosis microsurgery - Jing Wang; Ming Xing Hu; Min Lu; Xu Li (PLoS ONE, 2025)
Objective This study evaluated percutaneous lymphatic contrast-enhanced ultrasound (CEUS) for preoperative localization in preparation for lymphovenous anastomosis (LVA) microsurgery. Methods Fourteen healthy volunteers and 14 patients with lower limb lymphoedema were studied. SonoVue® (Bracco, Milan, Italy) was used to measure lymphatic vessel diameters and depths in the dorsal foot, ankle, and lower leg of the subjects. In the lymphoedema patients, lymphatic vessels were observed for continuity, distortion, dilation, interruption, and other abnormalities. On the basis of the CEUS images, the lower limb lymphatic vessels were categorized as normal, dilated, contracted, or sclerotic. In the lymphoedema patients, the locations of lymphatic vessels with good visibility were marked on the skin, and the accuracy of preoperative localization was evaluated based on the basis of surgical results. The data were analysed using IBM SPSS Statistics27.0 (IBM Corp., Armonk, NY, USA). Continuous data are expressed as the means ± standard deviations and were compared using paired t-tests, with P < 0.05 considered statistically significant. Results Among the healthy volunteers, one had a 1–2 mm lymphatic vessel visible in the dorsal foot, whereas 13 had no lymphatic vessels visible in the dorsal foot; however, lymphatic vessels were visible in the ankle and lower leg in all volunteers, with an average diameter of 0.42 ± 0.09 mm, resulting in a 100% visualization success rate. In lymphoedema patients, CEUS achieved a 92.86% success rate (13/14) in visualizing lymphatic vessels within 1 minute in lymphedema patients, excluding one patient with primary lymphoedema; the average vessel diameter was 0.66 ± 0.24 mm. The most common type consisted of dilated lymphatic vessels with tortuous morphology and increased diameter, often accompanied by reflux and interstitial dispersion in lymphoedema patients. With the successful intraoperative identification of lymphatic vessels under the surface marking during LVA as the standard, the accuracy of preoperative lymphatic vessel localization by CEUS was 92.36%. Conclusion CEUS can accurately localize functional lymphatic vessels and serves as a valuable complementary method to indocyanine green for preoperative lymphatic vessel mapping in LVA.